Variation of Thermal Infrared Brightness Temperature Anomalies in the Madoi Earthquake and Associated Earthquakes in the Qinghai-Tibetan Plateau (China) - Yang, Xing; Zhang, Tie-bao; Lu, Qian; Long, Feng; Liang, Ming-jian; Wu, Wei-wei; Gong, Yue; Wei, Jia-xi; Wu, Jia (Frontiers in Earth Science, 2022)
We processed MODIS data received from ground receiving stations into the spatial range of the Qinghai-Tibetan Plateau (China) and the eastern margin of the plateau, and then 283 K was set as the threshold value to remove the area covered by clouds. The monthly background field was calculated based on 17 years’ data, then we obtained the spatial Brightness Temperature anomaly of the current month by deducting the background field. Furthermore, the Brightness Temperature anomaly curves for secondary tectonic blocks in the plateau were calculated. The data indicated that since June 2020, the Brightness Temperature radiation within the Qinghai-Tibetan Plateau began to increase abnormally, starting from the western part of the study area and expanding eastward to cover the entire plateau. In January 2021, such an anomaly was seen again, extending to the Sichuan-Yunnan Block in the easternmost part of the study area in april. With the ongoing anomaly, a series of moderate and strong earthquakes occurred in the Qinghai-Tibetan Plateau, and finally, on 22 May 2021, the M7.4 earthquake struck the Madoi County. Moreover, according to the internal Brightness Temperature time series curves of the different secondary tectonic blocks, the Brightness Temperature has increased simultaneously since the beginning of 2020. A twofold standard deviation was found in the middle-east segment of the Bayanhar Block and the Qiangtang Block in October 2020, and an almost twofold standard deviation was found in March, while a twofold standard deviation was found in the Sichuan-Yunnan Block in april 2021. The occurrence of earthquakes in the plateau before the Madoi earthquake coincided with an upward trend of the time series curve. The spatial anomaly of Brightness Temperature over the Qinghai-Tibetan Plateau disappeared and the Brightness Temperature time series curve dropped drastically after the Madoi earthquake. The development of spatial anomaly of Brightness Temperature and the time series curve both coincide with the occurrence of earthquakes and are consistent with the generation of tectonic stress in the Qinghai-Tibetan Plateau. Our study showed that thermal infrared Brightness Temperature radiation reasonably reflects regional stress development and enables the detection of anomalies prior to moderate and strong earthquakes.